PREVALENCE AND ANTIBIOGRAM OF KLEBSIELLA SPECIES DETECTED IN CLINICAL - kaur, surender; Awari, Abhijit (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: We evaluated the prevalence rate and antibiogram of Klebsiella species isolated in various clinical samples, for effective management. Methods: The prospective study was undertaken to evaluate various clinical samples received in the microbiology laboratory for culture and sensitivity testing. Culture showing Klebsiella species were further processed for antibiotic susceptibility testing by the Kirby−Bauer disk diffusion test. Results: During the study period, 332 Klebsiella species were isolated in various samples and out of which 98.7% were Klebsiella pneumoniae and were predominately from urine samples (37%). All isolates were processed to determine their antibiogram. The highest antimicrobial resistance was observed for third and fourth-generation cephalosporines (more than 85%). Conclusion: It is concluded from our study that multidrug resistance K. pneumoniae are the emerging superbugs which require close monitoring and should be reported regularly which will guide clinicians in effectful management and thus help in preventing the spread of multidrug resistance Klebsiella and future threat.